Antibiotic Resistance, Polycentricity, and the Regulation of Antibiotic Prescribing in the Primary Care Setting - David J. Carter (Laws)
Antimicrobial resistance (AMR) is an urgent global challenge requiring an effective regulatory response, particularly regarding the governance of antibiotic prescribing. Dominant understandings of prescribing, however, are marked by a vision of the regulatory field with a strong ‘centre’—namely, the prescriber—whose actions are given a central role in directing the flow of events around AMR through a form of command-and-control rule. This insistence on a strong ‘centre’ and upon juridical forms of governance is de-centred in many contemporary conceptions of regulation. Drawing on data from interviews with patients who are enmeshed within AMR-related regulatory systems in the Australian primary care setting, this article argues that this regulatory field is polycentric in nature with signs that multiple regulatory actors influence prescribing and thus AMR-related outcomes. This polycentricity radically alters the capacity of individual actors to influence the flow of events around prescribing and indicates different regulatory approaches are required to realise objectives regarding AMR.